A case study to examine undergraduate students’ intention to use internet of things (IoT) services in the smart classroom - Ameer Alhasan, Ameer Alhasan; Mahmood H. Hussein, Mahmood H. Hussein; Lukman Audah, Lukman Audah; Ammar Al‑Sharaa, Ammar Al‑Sharaa; Ishaq Ibrahim, Ishaq Ibrahim; Moamin A. Mahmoud, Moamin A. Mahmoud (Springer, 2023)
Recently, the education sector has received increased interest in terms of the adoption of Internet of things (IoT) services for learning activities. However, despite this interest, empirical studies on the adoption of IoT services in the smart classroom are limited. Thus, the present study examines students’ intention to use IoT services in the smart classroom. Towards this end, an integrated model based on the technology acceptance model (TAM), technology readiness index (TRI), and external factors (enjoyment, compatibility, and self-efcacy) is proposed. A quantitative research design was therefore used to determine the factors that afect students’ intention to use IoT services in the smart classroom, using a sample of 230 participants. The fndings showed that compatibility, discomfort, enjoyment, and self-efcacy had a signifcant infuence on both perceived ease of use (PEoU) and perceived usefulness (PU). Furthermore, innovativeness had a signifcant efect on PEoU, and insecurity had a signifcant impact on PU. The results also revealed that PU had a signifcant infuence on the students’ behavioural intention to use. These fndings extend the understanding of students’ intention to use IoT services in the smart classroom. This study could be benefcial to researchers, educators, and IoT developers. However, it also presents a number of limitations, such as a lack of qualitative methods and the small number of theories applied.